A catalyst for selective oxidation of hydrocarbons and its preparation method and application

By introducing organic carbon in the precursor synthesis process of VPO catalyst and controlling the carbon content through heat treatment and activation processes, the problem of too low catalyst carbon content in the prior art is solved, and the selectivity and performance of the catalyst are improved.

CN116020502BActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111241522.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-25
Publication Date
2025-04-25
Estimated Expiration
2041-10-25

AI Technical Summary

Technical Problem

In the prior art, the carbon content of VPO catalysts is too low, which affects its selectivity and performance.

Method used

A vanadium phosphorus oxide catalyst was prepared by introducing organic carbon during the synthesis of the catalyst precursor and controlling the carbon content between 5% and 10% through the heat treatment and activation process.

Benefits of technology

The acid anhydride selectivity of catalysts in hydrocarbon selection oxidation reactions has been improved, and the application prospects of catalysts have been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116020502B_ABST
    Figure CN116020502B_ABST
Patent Text Reader

Abstract

The present invention discloses a catalyst for the selective oxidation reaction of hydrocarbons, which is a vanadium phosphorus oxide catalyst, wherein the vanadium phosphorus oxide catalyst comprises vanadium phosphorus oxide and an optional auxiliary element, and the catalyst comprises 5%-10% carbon based on the total weight of the catalyst. The present invention also discloses a preparation method of the catalyst and its application in the selective oxidation reaction of hydrocarbons to produce anhydrides. The catalyst of the present invention is used for the selective oxidation reaction of hydrocarbons to produce anhydrides, which can effectively improve the selectivity of anhydride products, and has a high application prospect for the gas phase catalytic oxidation of hydrocarbons, especially the gas phase oxidation reaction of n-butane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrocarbon selective oxidation catalyst preparation, and specifically relates to a catalyst for hydrocarbon selective oxidation reaction and a preparation method and application thereof. Background Art

[0002] Gas-phase selective oxidation of hydrocarbons is an important type of catalytic reaction, in which one of the typical products is maleic anhydride (MA).

[0003] Maleic anhydride, also known as maleic anhydride (MA), is a commonly used important organic chemical raw material and the third largest anhydride variety in the world. Its earliest production method used benzene as the production raw material, but due to environmental hazards and the influence of economic factors, the current mainstream production method of maleic anhydride uses n-butane as the production raw material, including fixed bed, fluidized bed, moving bed and other processes, each of which has its own characteristics and has practical industrial applications; and these different processes use the same type of catalyst.

[0004] Vanadium-containing oxides are often used as catalysts for selective oxidation reactions because of their good catalytic properties for redox reactions. Among them, vanadium phosphorus oxide (VPO) catalysts are by far the most effective catalysts for catalyzing the selective oxidation of gas-phase hydrocarbons, especially the oxidation of n-butane to produce maleic anhydride. VPO catalysts can be prepared from precursors using water or organic solvent methods. Early studies usually used pentavalent vanadium oxides such as vanadium pentoxide (V2O5) to react in the presence of water and HCl. Currently, VPO catalyst precursors are mainly prepared using organic methods. The preparation process usually uses pentavalent vanadium oxides and phosphoric acid to reflux in an organic solvent (mainly alcohols) to obtain the precursor. A large number of studies believe that the main phase composition of the active VPO catalyst precursor is VOHPO4·0.5H2O. However, for a VPO catalyst with good performance, the main phase composition is not the only determining factor. The VPO precursor prepared by the organic phase method generally contains residual carbon components in its powder, and these carbon components and the molding lubricant graphite constitute the carbon composition of the final molded catalyst. Studies have shown that the carbon in these catalysts will affect the performance of VPO catalysts to a certain extent, and the source of this carbon may be the additive graphite added during the molding process, or organic matter that is somehow fixed on the catalyst surface or remains in the catalyst structure.

[0005] For vanadium phosphorus oxide, there are two main sources of carbon, one is brought in the precursor synthesis process, and the other is introduced by molding aids such as graphite in the precursor molding process. The carbon in the precursor synthesis process is mainly organic carbon formed by organic solvents, which is determined by the organic content retained in the catalyst precursor in the common synthesis process in this field. These organic substances are removed to varying degrees during the heat treatment of the precursor due to the specific types, thereby forming a quantitative change in carbon content. Generally speaking, increasing the content of organic solvents such as benzyl alcohol with a higher residual amount will change the organic carbon content in the precursor and the activated catalyst, but because the solvent composition in the precursor preparation process has a greater correlation with the performance structure of the catalyst, the change will affect the catalyst performance to a greater extent. On the other hand, the graphite carbon introduced by molding aids such as graphite will move to the catalyst surface during its molding process, and the effect on the catalyst selectivity will be relatively small.

[0006] CN1353627A proposes a method for controlling the carbon content in a vanadium-phosphorus mixed oxide catalyst precursor. By changing the composition of the organic solvent in the precursor synthesis, introducing polyols and 300°C air treatment, the carbon content in the catalyst precursor can be controlled below 1.5%. CN1642641A mentions heat treatment of the obtained precursor to control the organic carbon content in the catalyst precursor to be less than 1.1%.

[0007] The above-mentioned VPO catalyst precursor usually needs to be treated by high-temperature activation to further obtain an active catalyst that can be used for selective oxidation reaction, which also means that the carbon content in the active catalyst may be further reduced due to the high-temperature activation process.

[0008] In general, existing technical solutions tend to reduce the carbon content in catalyst precursors as much as possible, believing that the presence of carbon in such precursors is not conducive to improving catalyst performance. There is a lack of research on the effect of the presence and content of carbon in the catalyst on catalyst performance, especially selectivity. Summary of the invention

[0009] In view of the problems existing in the prior art, the present invention has found through research that a certain amount of carbon in a certain form in the catalyst is conducive to improving the selectivity of the catalyst and is an effective way to improve the performance of the catalyst. Based on this, the present invention provides a new catalyst for selective oxidation of hydrocarbons through a preparation method for increasing the carbon content in the catalyst. The catalyst of the present invention has higher anhydride selectivity in the reaction of selective oxidation of hydrocarbons to produce anhydrides.

[0010] To this end, the first aspect of the present invention provides a catalyst for the selective oxidation reaction of hydrocarbons, which is a vanadium phosphorus oxide catalyst, wherein the vanadium phosphorus oxide catalyst comprises vanadium phosphorus oxide and optional auxiliary elements, and based on the total weight of the catalyst, the catalyst comprises 5%-10%, preferably 5%-8% carbon.

[0011] The second aspect of the present invention provides a method for preparing the catalyst according to the first aspect of the present invention, comprising the following steps:

[0012] (1) Concentrated phosphoric acid and an organic solvent I are mixed and then sealed and cooled to obtain a mixed solution I;

[0013] (2) mixing a vanadium source and an optional auxiliary element compound with an organic solvent II and heating the mixture to obtain a mixed solution II, and mixing the mixed solution II with the mixed solution I for reaction, and then performing solid-liquid separation, and optionally drying the mixture, and then mixing the dried solid with an organic solvent III for solid-liquid separation, and then drying to obtain a catalyst precursor;

[0014] (3) heat treating the obtained catalyst precursor;

[0015] (4) The heat-treated catalyst precursor is molded and then activated to obtain the catalyst.

[0016] The third aspect of the present invention provides an application of the catalyst described in the first aspect of the present invention and / or the catalyst prepared by the preparation method described in the second aspect of the present invention in the selective oxidation of hydrocarbons to produce acid anhydrides, especially the selective oxidation of n-butane to produce maleic anhydride.

[0017] Compared with the prior art, the present invention adopts a synthesis method of effectively introducing organic carbon in the synthesis process of the catalyst precursor, and after effective molding and activation heat treatment, the carbon content in the final activated catalyst can be controlled to be 5%-10%. The catalyst of the present invention can effectively improve the selectivity of the anhydride product when used in the selective oxidation of hydrocarbons to produce anhydrides, and has a high application prospect in the gas phase catalytic oxidation of hydrocarbons, especially the gas phase oxidation reaction of n-butane. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD pattern of the catalyst in Example 1.

[0019] Figure 2 XRD diagram of the catalyst in Comparative Example 1 DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] According to the present invention, the first aspect of the present invention provides a catalyst for the selective oxidation reaction of hydrocarbons, which is a vanadium phosphorus oxide catalyst. The vanadium phosphorus oxide catalyst comprises vanadium phosphorus oxide and optional auxiliary elements, and based on the total weight of the catalyst, the catalyst comprises 5%-10% carbon.

[0022] According to some embodiments of the present invention, the catalyst comprises 5%-8% carbon, based on the total weight of the catalyst.

[0023] According to some embodiments of the invention, at least 70 wt % of the carbon is amorphous carbon.

[0024] According to some embodiments of the invention, at least 80 wt%, at least 90 wt% or 100 wt% of the carbon is amorphous carbon.

[0025] According to some embodiments of the present invention, the carbon contains 0-30wt% crystalline carbon based on the total weight of the carbon, for example, the crystalline carbon in the carbon accounts for 5wt%, 10wt%, 15wt%, 20wt%, 25wt% and any value therebetween.

[0026] According to some preferred embodiments of the present invention, based on the total weight of the catalyst, the content of the amorphous carbon is ≥ 4%. In some embodiments, the content of the amorphous carbon is ≥ 5%.

[0027] According to some embodiments of the present invention, the amorphous carbon comes from a carbon-containing organic compound added during the catalyst preparation process, such as a carbon-containing organic solvent added during the catalyst preparation process.

[0028] According to some embodiments of the present invention, the crystalline carbon comes from inorganic carbon added during the catalyst preparation process, for example, inorganic carbon added during the catalyst molding process such as molding aid graphite.

[0029] According to some embodiments of the present invention, in the XRD diffraction spectrum of the catalyst, the ratio of the peak height I1 of the diffraction peak at 2θ=22.8 and the peak height I2 of the diffraction peak at 2θ=26.5 is I1:I2=(0.3-2):1, and the ratio of the peak height I1 of the diffraction peak at 2θ=22.8 and the peak height I3 of the diffraction peak at 2θ=28.4 is I1:I3>1, preferably (1-2):1. Among them, the diffraction peaks at 2θ=22.8 and 28.4 correspond to the (020) and (204) crystal planes of the pyrophosphate vanadium phase of the catalyst, and the diffraction peak at 2θ=26.5 corresponds to the diffraction characteristic peak of graphite in the catalyst, which shows that the carbon content in the catalyst is not mainly contributed by the addition of graphite carbon during molding.

[0030] According to the present invention, the promoter element is an element that helps the selective oxidation reaction of hydrocarbons. The selection range of the promoter element is relatively wide and can be selected based on the purpose of improving different properties of the catalyst. In some embodiments, the promoter element is selected from at least one of IIIA, IVA, VA, IVB, VB, VIB groups and rare earth elements. In some embodiments, the promoter element is molybdenum.

[0031] According to some embodiments of the present invention, the vanadium phosphorus oxide catalyst has a composition as shown in the formula VPxMyOz, wherein x=1-2, preferably 1-1.5; y=0-0.5, preferably 0-0.2, z is any value that satisfies the molecular formula to be neutral, and M is the auxiliary element.

[0032] The second aspect of the present invention provides a method for preparing the catalyst according to the first aspect of the present invention, comprising the following steps:

[0033] (1) Concentrated phosphoric acid and an organic solvent I are mixed and then sealed and cooled to obtain a mixed solution I;

[0034] (2) mixing a vanadium source and an optional auxiliary element compound with an organic solvent II and heating the mixture to obtain a mixed solution II, mixing the mixed solution II with the mixed solution I for reaction, and then performing solid-liquid separation, optionally drying the mixture, and mixing the dried solid with an organic solvent III for solid-liquid separation, and then drying to obtain a catalyst precursor;

[0035] (3) heat treating the obtained catalyst precursor;

[0036] (4) The heat-treated catalyst precursor is molded and then activated to obtain the catalyst.

[0037] According to the present invention, the "concentrated phosphoric acid" in the present invention does not only represent phosphoric acid with a concentration of 85% in the conventional sense, but also includes high-concentration phosphoric acid with a higher concentration. Those skilled in the art know that the concentration of conventional concentrated phosphoric acid is 85%. If phosphoric anhydride such as P2O5 is continuously added thereto, its concentration will increase, and it is generally orthophosphoric acid at this time. When the concentration reaches 100%, the anhydride is continued to be added, and the phosphoric acid begins to partially dehydrate, and the composition becomes complicated, and pyrophosphoric acid, polyphosphoric acid, etc. are formed, and these are all within the scope of the "concentrated phosphoric acid" in the present invention.

[0038] According to some embodiments of the present invention, the concentrated phosphoric acid in step (1) is a high-concentration phosphoric acid with dehydration properties, preferably the concentrated phosphoric acid has a weight concentration of 100%-110% in terms of H3PO4, preferably 101%-105%, and is more preferably selected from at least one of orthophosphoric acid, pyrophosphoric acid, and phosphoric acid polymers.

[0039] According to the present invention, the vanadium source can be any vanadium compound known in the art for preparing vanadium phosphorus oxide catalysts. Preferably, the vanadium source is selected from at least one of vanadium pentoxide, ammonium metavanadate and organic vanadium acid, more preferably vanadium pentoxide.

[0040] According to the present invention, the auxiliary element compound has a wide selection range and can be a compound of the auxiliary element soluble in organic solvent II, preferably at least one of an acid and a salt of the auxiliary element soluble in organic solvent II. In some embodiments, the auxiliary element compound is an acid or salt of molybdenum, such as phosphomolybdic acid.

[0041] According to the present invention, the organic solvent I is selected from at least one of alcohol organic solvents, preferably at least one of monohydric alcohol and polyhydric alcohol. According to some preferred embodiments of the present invention, the organic solvent I is selected from C4-C6 monohydric alcohol, preferably isobutanol.

[0042] According to the present invention, the organic solvent II is selected from at least one of alcohol and organic acid organic solvents, such as at least one of monohydric alcohol, polyhydric alcohol and organic acid, and the organic acid is, for example, fatty acid.

[0043] In some preferred embodiments, the organic solvent II is selected from C4-C6 fatty alcohols and C7-C 10 At least one of the aromatic alcohols, more preferably isobutyl alcohol and / or benzyl alcohol.

[0044] According to the present invention, the organic solvent II may be the same as or different from the organic solvent I; preferably, in the primary catalyst preparation step, the organic solvent I is selected from one or more of the organic solvents II.

[0045] According to some embodiments of the present invention, in step (1), the mass ratio of the concentrated phosphoric acid to the organic solvent I is (1-5):1, preferably (1.5-4):1, and more preferably (1.5-3):1.

[0046] According to some embodiments of the present invention, in step (1), the mixing temperature is 80-120°C.

[0047] According to some embodiments of the present invention, in step (1), the mixing time is 0.5-3h.

[0048] In some embodiments, in step (2), the mass of the organic solvent II is not less than 4 times the total mass of the vanadium source and the optional auxiliary element compound, preferably 4-20 times, and more preferably 4-15 times.

[0049] According to some embodiments of the present invention, the mixed reaction in step (2) is carried out by heating under reflux, and preferably the heating under reflux time is 2-24 hours. The heating under reflux temperature depends on the solvent composition and pressure change. In some embodiments, the heating under reflux temperature is 103-120°C.

[0050] According to some embodiments of the present invention, in step (2), the mixed reaction of the mixed solution II and the mixed solution I is carried out by quantitatively adding the mixed solution I to the mixed solution II, wherein the amount of the mixed solution I is determined by the required phosphorus-vanadium ratio, and the time of adding the mixed solution I can be selected to be during the heating process or the reflux process of the mixed solution II; preferably, the mixed solution I is added during the heating process; more preferably, the mixed solution I is added during the heating process and the addition is completed before the reflux temperature is reached.

[0051] According to some embodiments of the present invention, the method of quantitatively adding the mixed solution I to the mixed solution II is not clearly limited, and it can be added all at once or added dropwise at a certain speed; preferably, it is added dropwise.

[0052] According to the present invention, the mixing method is not specifically limited, and is based on the principle of fully contacting the added raw materials. Conventional mixing methods in the art, such as stirring, can be used.

[0053] According to the present invention, the method of solid-liquid separation is not clearly defined. The solid-liquid separation refers to the process of cooling the mixed solution after the catalyst precursor synthesis process is completed, and then separating the solvent from the catalyst precursor by solid-liquid separation. As is well known to researchers in the field, solid-liquid separation can be achieved by filtering, centrifuging and other treatment methods. In the solid-liquid separation process, the catalyst precursor can be washed after separation from the solvent. The washing solvent is usually selected from organic solvents that are easy to volatilize or can be easily removed by heat treatment, such as monohydric alcohols and acetone. It is also possible to choose not to wash. The above treatment does not affect the realization of the characteristics of the present invention.

[0054] According to the present invention, the drying method is not clearly defined, and a drying method known to those skilled in the art can be used, and the drying can be carried out in air, inert gas, or a mixed atmosphere thereof, or in an environment with a high degree of vacuum, without affecting the realization of the technical features of the present technical solution. In some preferred embodiments, the drying temperature is 70-200°C, preferably 110-150°C.

[0055] According to some embodiments of the present invention, the organic solvent III is selected from at least one of an alcohol organic solvent and an ester organic solvent, the alcohol organic solvent is preferably a monohydric alcohol, a dihydric alcohol and a polyhydric alcohol, such as a C2-C6 fatty alcohol, and the ester organic solvent is preferably a phosphate ester, preferably a C3-C6 fatty phosphate ester. According to some preferred embodiments of the present invention, the organic solvent III is selected from ethylene glycol and / or triethyl phosphate, more preferably a mixture of ethylene glycol and triethyl phosphate.

[0056] According to the present invention, in step (2), the solid obtained by the first drying is preferably stirred and mixed in an organic solvent III at 50-150° C. for 0.5-6 h, and then solid-liquid separation and drying are performed again, but the absence of this step does not affect the realization of the technical characteristics of the catalyst.

[0057] According to some embodiments of the present invention, in step (3), the heat treatment can remove some of the carbon and high-boiling point organic solvents that are simply adsorbed and remain in the catalyst precursor, which is beneficial to reducing the thermal effect of the catalyst during high-temperature activation. However, too high a heat treatment temperature affects the catalyst performance. Therefore, the heat treatment temperature is 200-300°C, preferably 200-260°C.

[0058] According to some embodiments of the present invention, the heat treatment time is 1-20 hours, preferably 2-16 hours.

[0059] According to the present invention, the molding in step (4) can be performed by molding into a certain shape using a molding method well known to those skilled in the art, such as extrusion or tableting. The shape of the molded catalyst can be spherical, cylindrical, hollow cylindrical or other shaped sheet structures with a certain porosity; preferably, the catalyst is hollow cylindrical.

[0060] According to some embodiments of the present invention, the molding process in step (4) is carried out by adding a molding aid, and the molding aid can be a lubricating agent well known to those skilled in the art, such as graphite. The amount of molding aid used must take into account its effect on the catalyst performance. The use of carbon-containing additives such as graphite will introduce graphite carbon into the catalyst composition to a certain extent. Although not all of the graphite carbon will remain in the activated catalyst after activation, it still partially affects the total carbon content in the catalyst. Excessive content of this graphite carbon may have an adverse effect on the catalyst performance. In the technical solution of the present invention, high carbon content is not achieved by increasing the amount of carbon-containing additives such as graphite. Usually, the amount of graphite added is controlled within 4%, which is reflected in the XRD spectrum of the final catalyst. Figure 2 The intensity of the characteristic diffraction peak at θ=26.5 is usually also controlled within a reasonable range.

[0061] According to some embodiments of the present invention, the activation in step (4) includes heat treatment activation, which can further activate the catalyst precursor into an activated catalyst that can be used for the selective oxidation reaction.

[0062] According to some embodiments of the present invention, the heat treatment activation comprises heating the catalyst precursor in a mixed atmosphere, and preferably the temperature of the heat treatment activation is 200-550° C., and the time of the heat treatment activation is 2-24 h.

[0063] According to some embodiments of the present invention, the mixed atmosphere includes one or more of molecular oxygen-containing gas, inert gas, water vapor, carbon oxides, and organic phosphates.

[0064] According to some embodiments of the present invention, the molecular oxygen-containing gas is air or oxygen.

[0065] According to some embodiments of the present invention, the inert gas is at least one of nitrogen, helium and argon.

[0066] The third aspect of the present invention provides an application of the catalyst described in the first aspect of the present invention and / or the catalyst prepared by the preparation method described in the second aspect of the present invention in the selective oxidation of hydrocarbons to produce acid anhydrides, especially the gas phase oxidation of n-butane to produce maleic anhydride.

[0067] According to the present invention, the scheme of the present invention is different from the common catalyst scheme of this type in that a specific type of carbon is introduced and other carbon elements that are detrimental to the catalytic reaction are removed through a subsequent activation process, thereby effectively increasing the carbon content of the final activated catalyst without reducing the catalytic effect of the catalyst, thereby improving the catalyst selectivity.

[0068] According to the present invention, unless otherwise specified, cooling refers to cooling to room temperature.

[0069] According to the present invention, "optional" may mean containing or not containing, and may also mean adding or not adding.

[0070] To make the present invention easier to understand, the present invention will be described in detail below in conjunction with examples and drawings. These examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the materials used in the examples are all commercially available products or conventional products that can be synthesized by known methods.

[0071] The carbon content in the present invention is obtained by testing the finished catalyst using a carbon-sulfur analyzer.

[0072] The catalyst prepared in the present invention is evaluated by the following scheme: the catalyst is placed in a fixed bed reactor, the raw material is a mixture of n-butane and air with a volume concentration of 1.5%, and maleic anhydride is produced by gas phase catalytic reaction. Reaction process conditions: space velocity is 2000hr -1 , the reaction temperature is 350-500°C, and the reaction pressure is normal pressure. The above evaluation scheme is only used to evaluate the performance of the comparative catalyst, and does not limit the reaction application conditions of the catalyst of the present invention.

[0073] Example 1

[0074] (1) Preparation of catalyst

[0075] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 15g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the obtained solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h. It was heated to 260°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 2% of the weight of the obtained powder was added and the powder was pressed into hollow cylindrical particles with an outer diameter of about 6 mm and an inner pore diameter of about 2.5 mm. Subsequently, the temperature was slowly raised to 500°C in 35% air / 35% nitrogen / 5% carbon dioxide / 25% water vapor, and the mixture was calcined and kept warm for 3 h to obtain an active catalyst.

[0076] Results The carbon content of the catalyst was 6.5 wt % as measured by the carbon sulfur analyzer. The XRD spectrum of the catalyst at 2θ = 20-32° shows Figure 1 , wherein the catalyst has a diffraction peak height I1 at 2θ=22.8 and a diffraction peak height I2 at 2θ=26.5 in the XRD diffraction spectrum at a ratio of I1:I2=1.4, while a diffraction peak height I1 at 2θ=22.8 and a diffraction peak height I3 at 2θ=28.4 have a ratio of I1:I3 of 1.1, wherein the crystalline carbon from graphite and the like in the total carbon content accounts for 1% of the total weight of the catalyst, and the calculated content of amorphous carbon from organic carbon-containing solvents is greater than 5% (amorphous, not shown in the XRD pattern).

[0077] (2) Catalyst performance evaluation

[0078] The prepared catalyst was placed in a fixed bed reactor, and a mixed raw material gas of n-butane and air was introduced, wherein the content of n-butane was 1.5 vol%, and maleic anhydride was produced through gas phase catalytic reaction. Reaction process conditions: feed space velocity of 2000 hr -1 , the reaction temperature is 425°C, the reaction pressure is normal pressure, and the reaction time is 100h.

[0079] The results showed that the molar conversion of n-butane was 78.5% and the molar selectivity of maleic anhydride was 73.9%.

[0080] Example 2

[0081] (1) Preparation of catalyst

[0082] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 15g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the obtained solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h, heated to 300°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 2% of the weight of the obtained powder was added and tableted into hollow cylindrical particles as in Example 1. Subsequently, the temperature was slowly raised to 500°C in air / nitrogen / carbon dioxide / water vapor, calcined and kept warm for 3 h to obtain an active catalyst.

[0083] Results The carbon content of the catalyst was 5.5 wt % as measured by a carbon-sulfur instrument.

[0084] (2) Catalyst performance evaluation

[0085] The method was the same as that of Example 1. The results showed that the n-butane conversion was 81.5% and the maleic anhydride selectivity was 70.3%.

[0086] Example 3

[0087] (1) Preparation of catalyst

[0088] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 15g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. Heat to 260°C in an air atmosphere and keep warm for 6 hours. After cooling the obtained powder, add a graphite additive equivalent to 2% of the weight of the obtained powder and press it into hollow cylindrical particles as in Example 1. Then slowly heat to 500°C in air / nitrogen / carbon dioxide / water vapor, calcine and keep warm for 3 hours to obtain an active catalyst.

[0089] Results The carbon content of the catalyst was 6.3 wt % as measured by a carbon-sulfur analyzer.

[0090] (2) Catalyst performance evaluation

[0091] The method was the same as that of Example 1. The results showed that the n-butane conversion was 82.7% and the maleic anhydride selectivity was 69.0%.

[0092] Example 4

[0093] (1) Preparation of catalyst

[0094] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 15g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h. It was heated to 260°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 4% of the weight of the obtained powder was added and tableted into hollow cylindrical particles as in Example 1. Subsequently, the temperature was slowly raised to 500°C in air / nitrogen / carbon dioxide / water vapor, calcined and kept warm for 3 h to obtain an active catalyst.

[0095] Results The carbon content of the catalyst was 6.9 wt % as measured by a carbon-sulfur analyzer.

[0096] (2) Catalyst performance evaluation

[0097] The method was the same as that of Example 1, and the n-butane conversion was measured to be 78.7 mol% and the maleic anhydride selectivity was 72.6 mol%.

[0098] Example 5

[0099] (1) Preparation of catalyst

[0100] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 10g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h. It was heated to 260°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 2% of the weight of the obtained powder was added and tableted into hollow cylindrical particles as in Example 1. Subsequently, the temperature was slowly raised to 500°C in air / nitrogen / carbon dioxide / water vapor, calcined and kept warm for 3 h to obtain an active catalyst.

[0101] Results The carbon content of the catalyst was 5.4 wt % as measured by a carbon-sulfur analyzer.

[0102] (2) Catalyst performance evaluation

[0103] The method was the same as that of Example 1. The results showed that the n-butane conversion was 80.9% and the maleic anhydride selectivity was 71.9%.

[0104] Example 6

[0105] (1) Preparation of catalyst

[0106] 35.9g of concentrated phosphoric acid (105% H3PO4) was slowly added to 20g of isobutanol and mixed, and heated to 100°C for reaction for 30min under stirring, and then the solution was sealed and cooled to obtain mixed solution I. 25g of vanadium pentoxide and 0.2g of phosphomolybdic acid were added to a mixed solution of 200ml of isobutanol and 50ml of benzyl alcohol, and heated under stirring to obtain mixed solution II, and the mixed solution I prepared above was added dropwise to the mixed solution II, and the solution temperature was about 100°C at the end of the addition. The mixed solution was continued to be heated to reflux, and after reflux for 20h, the mixed solution was cooled and filtered and washed with isobutanol, and the obtained filter cake was vacuum dried at 120°C for 20h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h. It was heated to 260°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 2% of the weight of the obtained powder was added and tableted into hollow cylindrical particles as in Example 1. Subsequently, the temperature was slowly raised to 500°C in air / nitrogen / carbon dioxide / water vapor, calcined and kept warm for 3 h to obtain an active catalyst.

[0107] Results The carbon content of the catalyst was 6.7 wt % as measured by a carbon-sulfur analyzer.

[0108] (2) Catalyst performance evaluation

[0109] The method was the same as that of Example 1. The results showed that the n-butane conversion was 77.6% and the maleic anhydride selectivity was 72.7%.

[0110] Comparative Example 1

[0111] (1) Preparation of catalyst

[0112] 25 g of vanadium pentoxide and 0.2 g of phosphomolybdic acid were added to a mixed solution of 200 ml of isobutyl alcohol and 50 ml of benzyl alcohol, and heated under stirring. At the same time, 35.9 g of concentrated phosphoric acid (105% H3PO4) was added dropwise to the mixed solution. The solution temperature was about 100° C. The mixed solution was continued to be heated to reflux. After reflux for 20 h, the mixed solution was cooled and filtered and washed with isobutyl alcohol. The obtained filter cake was vacuum dried at 120° C. for 20 h to obtain a catalyst precursor. The obtained catalyst precursor was heated to 70°C in ethylene glycol / triethyl phosphate (98% / 2% by mass) and stirred for 1 h. After filtering, it was dried at 110°C for 20 h. It was heated to 260°C in an air atmosphere and kept warm for 6 h. After the obtained powder was cooled, a graphite additive equivalent to 2% of the weight of the obtained powder was added and the powder was pressed into hollow cylindrical particles as in Example 1. Subsequently, the temperature was slowly raised to 500°C in air / nitrogen / carbon dioxide / water vapor, calcined and kept warm for 3 h to obtain an active catalyst.

[0113] Results The carbon content of the catalyst was 2.1 wt% as measured by a carbon sulfur analyzer. The characteristic XRD spectrum of the catalyst at 2θ = 20-32° is shown in Figure 2 , wherein the catalyst has a diffraction peak height I1 at 2θ=22.8 and a diffraction peak height I2 at 2θ=26.5 in the XRD diffraction spectrum with a ratio I1:I2=1.4, and a diffraction peak height I1 at 2θ=22.8 and a diffraction peak height I3 at 2θ=28.4 with a ratio I1:I3 of 0.9.

[0114] (2) Catalyst performance evaluation

[0115] The method was the same as that of Example 1. The results showed that the n-butane conversion was 89.5% and the maleic anhydride selectivity was 61.1%.

[0116] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A catalyst for the selective oxidation reaction of hydrocarbons, which is a vanadium phosphorus oxide catalyst, the vanadium phosphorus oxide catalyst comprising vanadium phosphorus oxide and an optional promoter element, and the catalyst comprises 5% to 10% carbon based on the total weight of the catalyst, Based on the total weight of the carbon, at least 70 wt % of the carbon is amorphous carbon, and the carbon contains 0-30 wt % of crystalline carbon; In the XRD diffraction spectrum of the catalyst, the diffraction peak height at 2θ=22.8 is I Diffraction peak height at 1 and 2θ=26.5 I 2 Ratio I 1: I 2=(0.3-2):1, diffraction peak height at 2θ=22.8 I The diffraction peak heights at 1 and 2θ=28.4 I 3. Proportion I 1: I 3>1.

2. The catalyst according to claim 1, characterized in that The content of amorphous carbon is ≥ 4% based on the total weight of the catalyst. and / or the amorphous carbon comes from a carbon-containing organic solvent added during the catalyst preparation process; And / or the catalyst comprises 5%-8% carbon.

3. The catalyst according to claim 1 or 2, characterized in that The crystalline carbon comes from the inorganic carbon added during the catalyst forming process. And / or in the XRD diffraction spectrum of the catalyst, the diffraction peak height at 2θ=22.8 I The diffraction peak heights at 1 and 2θ=28.4 I 3. Proportion I 1: I 3=(1.1-2):

1.

4. The catalyst according to claim 1 or 2, characterized in that The auxiliary element is selected from at least one of the IIIA, IVA, VA, IVB, VB, VIB groups and rare earth elements; And / or the vanadium phosphorus oxide catalyst has a composition as shown in the formula VPxMyOz, wherein x=1-2; y=0-0.5, z is any value that satisfies the molecular formula and is neutral, and M is the auxiliary element.

5. The catalyst according to claim 4, characterized in that The auxiliary element is molybdenum; And / or, x=1-1.5; y=0-0.

2.

6. A method for preparing a catalyst as described in any one of claims 1 to 5, comprising the following steps: (1) Concentrated phosphoric acid and an organic solvent I are mixed and then sealed and cooled to obtain a mixed solution I; (2) mixing a vanadium source and an optional auxiliary element compound with an organic solvent II and heating the mixture to obtain a mixed solution II, mixing the mixed solution II with the mixed solution I for reaction, and then performing solid-liquid separation, optionally drying the mixture, and mixing the dried solid with an organic solvent III for solid-liquid separation, and then drying to obtain a catalyst precursor; (3) heat treating the obtained catalyst precursor; (4) The heat-treated catalyst precursor is molded and then activated to obtain the catalyst.

7. The preparation method according to claim 6, characterized in that: The concentrated phosphoric acid is a high-concentration phosphoric acid with dehydration properties; and / or the vanadium source is selected from at least one of vanadium pentoxide, ammonium metavanadate and organic acid vanadium; and / or the auxiliary element compound is at least one of an acid and a salt of the auxiliary element soluble in the organic solvent II; And / or the organic solvent I is selected from at least one of alcohol organic solvents; and / or the organic solvent II is selected from at least one of alcohol and organic acid organic solvents; and / or the organic solvent III is selected from at least one of alcohol organic solvents and ester organic solvents.

8. The preparation method according to claim 7, characterized in that: The concentrated phosphoric acid is phosphoric acid having a weight concentration of 100%-110% in terms of H3PO4; and / or the organic solvent I is selected from a C4-C6 monohydric alcohol; and / or the organic solvent II is selected from a C4-C6 fatty alcohol and a C7-C 10 and / or the organic solvent III is selected from at least one of C2-C6 fatty alcohols and C3-C6 fatty phosphates.

9. The preparation method according to claim 8, characterized in that: The concentrated phosphoric acid is selected from at least one of orthophosphoric acid, pyrophosphoric acid and phosphoric acid polymer; And / or the organic solvent I is isobutanol; and / or the organic solvent II is selected from isobutanol and / or benzyl alcohol; and / or the organic solvent III is selected from ethylene glycol and / or triethyl phosphate.

10. The preparation method according to claim 9, characterized in that: The organic solvent III is a mixture of ethylene glycol and triethyl phosphate.

11. The preparation method according to any one of claims 6 to 10, characterized in that: In step (1), the mass ratio of concentrated phosphoric acid to organic solvent I is (1-5):

1.

12. The preparation method according to claim 11, characterized in that: In step (1), the mass ratio of concentrated phosphoric acid to organic solvent I is (1.5-4):

1.

13. The preparation method according to any one of claims 6 to 10, characterized in that: In step (1), the mixing temperature is 80-120°C, and the mixing time is 0.5-3h; and / or in step (2), the mixing reaction is carried out by heating under reflux; and / or in step (3), the heat treatment temperature is 200-300°C, and the heat treatment time is 1-20h.

14. The preparation method according to claim 13, characterized in that: The heating reflux time in step (2) is 2-24 hours; and / or the heat treatment temperature in step (3) is 200-260° C., and the heat treatment time is 2-16 hours.

15. The preparation method according to any one of claims 6 to 10, characterized in that: The molding process in step (4) is carried out by adding a molding aid; And / or the activation in step (4) is heat treatment activation, and the heat treatment activation includes heating the catalyst precursor in a mixed atmosphere.

16. The preparation method according to claim 15, characterized in that: The molding aid is a carbon-containing aid; And / or the temperature of the heat treatment activation is 200-550°C, and the time of the heat treatment activation is 2-24h.

17. The preparation method according to claim 16, characterized in that: The amount of the carbon-containing additive added is no more than 4% based on the mass of the catalyst precursor.

18. Use of the catalyst according to any one of claims 1 to 5 and / or the catalyst prepared by the preparation method according to any one of claims 6 to 17 in the selective oxidation of hydrocarbons to produce acid anhydrides.

19. The use according to claim 18, characterized in that The application is the application in the reaction of preparing maleic anhydride by gas phase oxidation of n-butane.

Citation Information

Patent Citations

  • Vanadium / phosphorus mixed oxide catalyst precursor

    CN1353627A

  • Catalyst-precursor for the production of maleic acid anhydride and method for the production thereof

    CN1642641A

  • Vanadium-phosphorus catalyst and preparation method thereof

    CN105413725A

  • Vanadium-phosphorus-oxide catalyst, preparation method and application thereof

    CN106622316A